ANALISIS MOTIVASI DAN KESADARAN BELAJAR WARGA BELAJAR DALAM PERSPEKTIF FILSAFAT PENDIDIKAN MASYARAKAT DI PKBM TAMAN BELAJAR MASYARAKAT - Anisa Nur Baidah Ginting; Salwa Zahra; Sasta Glovia Talenta Purba; Elizon Nainggolan; Michael Yudha Pratama (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. This study aims to analyze the motivation and learning awareness of learners at the Community Learning Center (PKBM) Taman Belajar Masyarakat (Community Learning Center), Jl. Pukas Raya No. 36, Bandar Klippa Village, Percut Sei Tuan District, Deli Serdang Regency, from the perspective of the Community Education Philosophy. The study used a descriptive qualitative approach, collecting data through observation, interviews with administrators, tutors, and learners, and photographic documentation. The results indicate that the motivation and learning awareness of learners are diverse and partly low, especially among participants who participate in the program solely to obtain a diploma. Learners with intrinsic motivation are more active and consistent, while the role of tutors through a personal approach and interactive learning methods has proven significant in increasing participation and learning awareness. These findings confirm that the success of learning in PKBM is influenced by the synergy between learners' internal motivation, tutor support, and a conducive learning environment, in line with the principles of empowerment and independence in the community education philosophy.